Digital Identification and ICT-Driven Development in Africa - Nirupam Bajpai; John Biberman (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
In recent years, countries across the African continent have begun implementing solutions based on Information and Communications Technology (ICT) for challenges ranging across the spectrum of sustainable development. The programs which have been implemented so far have produced impressive results, and in aggregate, they demonstrate the potential of a digital Africa which applies ICT to accelerate the improvement of human development outcomes in the pursuit of a more prosperous, equitable society. However, for these programs to live up to their full potential, they must be coupled with comprehensive, national digital identity systems. Digital identification not only boosts the efficiency of individual ICT-driven development initiatives, they permit seamless coordination between both public and private programs at all levels. While some African countries have established digital identity systems, but there is room for improvement in order to make them fully inclusive, transparent, and effective. In this, African governments can use India's Aadhaar digital identity system as a model for how to accomplish these objectives within the framework of a universal, highly integrated system, even under constraints of limited resources.
Keywords: 330